Physical and mechanical properties of mortar using waste Polyethylene Terephthalate bottles - Ge, Zhi; Sun, Renjuan; Zhang, Kun; Gao, Zhili; Li, Pengcheng (Construction & building materials, 2013)
•Recycled Polyethylene Terephthalate (PET) bottles were used as binder to produce plastic mortar.•Effects of gradation, sand-to-PET ratio, and curing time and temperature on compressive strength of mortar were studied.•Plastic mortar with continuously graded sand had higher compressive strength. The optimal sand-to-PET ratio was 3:1.•Mortar obtained over 90% of its 7-day strength within 3h.•Mortar cured under higher temperature gained high compressive strength. This paper studied the effects of aggregate gradation, sand-to-Polyethylene Terephthalate (PET) ratio, and curing conditions on physical and mechanical properties of recycled PET mortar. Infrared Spectrum test was performed to investigate the mechanism of strength development. Test results indicated that recycled PET mortar with continuously graded sand exhibited higher strength compared with mortar with single-sized gradation. As the sand-to-PET ratio increased, the compressive and flexural strength of recycled PET mortar increased. Compressive strength could reach 30MPa within 3h, which was over 90% of its 7-day strength. Samples cured under higher temperature had higher strength compared with specimens cured under low temperature. The curing time did not significantly influence the strength development. Infrared Spectrum test showed that more crystal was formed under higher curing temperature. This study reveals an innovative, easily implemented method to create a new mortar material by recycling waste PET bottles.